Harnessing the potential of tobacco cessation programme amidst COVID-19 pandemic in India - Bhatt, Garima; Goel, Sonu (Indian Journal of Community Health, 2020)
The COVID-19 pandemic of the 21st Century continues to spread, and tobacco users are at a higher risk of contracting the disease. As a measure to contain its spread, many nations have called for various measures like maintaining social distancing norms, the prohibition of spitting in the public place, partial or complete lockdown, and many more. This shutdown episode has disrupted the entire supply chain in our country, and it is quite natural that tobacco users are also experiencing a scarcity of tobacco products, like others. This adverse situation is an opportune moment for the Indian health systems to target tobacco users to motivate, facilitate, and support the cessation process. Additionally, social distancing can be achieved by utilizing and optimizing our existing health services. In our country, we have dedicated regional & national quitlines and m-Cessation facilities for tobacco users who are willing to quit. These initiatives could reduce the risk of COVID among tobacco users, facilitate the tobacco cessation movement, and provide credence to the advocacy for increasing taxes on tobacco products in the country.